Penerapan Algoritma N-GRAM Dan WINNOWING Untuk Deteksi Plagiarisme Usulan Dokumen Perguruan Tinggi - Adiat Pariddudin; Muhammad Jihad Abdul Fatah (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2022)
Plagiarism which is a disgraceful act can occur in any series of documents, including one of them is a feasibility study book document as is often made by universities, foundations of organizing bodies, to consultants related to the interests of establishing universities as well as proposals for opening new study programs submitted to the Ministry of Education and Culture and Higher Education (Kemendikbud Dikti). Consultants, especially those with legal entities, will determine the smoothness of proposals to rejection of proposals due to flaws in the text, the most common of which is plagiarism, which requires consultants to remain skilled in ensuring the authentication of documents made to clients as well as to the institution or institution that is the evaluator. This plagiarism can be prevented by building a plagiarism detection system with a programming algorithm approach such as; The second N-Gram Algorithm and Winnowing Algorithm were successfully built by researchers using the Research and Development (R&D) method to detect plagiarism in the proposed college documents, in this case training documents and test documents in the form of systems and applications. The application is made web-based by utilizing an interface to make it easier for leaders to ensure the similarity and authentication of documents made by consultants. The n-gram algorithm is a document processing method that is usually used in spelling correction, word prediction and other processing and Winnowing Algorithm is one of the algorithms in the document fingerprinting method. Both are used to detect Plagiarism of Proposed College Documents with the Feasibility Study Book document object resulting in a level of accuracy and effectiveness with the parameters of similarity between documents as stated in the percentage of similarity (similarity percentage) which can be concluded the value of plagiarism between documents.